2014
DOI: 10.1523/jneurosci.4690-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Astrocyte Glutamate Transporter GLT1 Exacerbates Phrenic Motor Neuron Degeneration, Diaphragm Compromise, and Forelimb Motor Dysfunction following Cervical Contusion Spinal Cord Injury

Abstract: A major portion of spinal cord injury (SCI) cases affect midcervical levels, the location of the phrenic motor neuron (PhMN) pool that innervates the diaphragm. While initial trauma is uncontrollable, a valuable opportunity exists in the hours to days following SCI for preventing PhMN loss and consequent respiratory dysfunction that occurs during secondary degeneration. One of the primary causes of secondary injury is excitotoxic cell death due to dysregulation of extracellular glutamate homeostasis. GLT1, mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 78 publications
2
68
1
Order By: Relevance
“…Failure of long-term extrasynaptic glutamate clearance is suspected to be one major cause of secondary cell loss following SCI. Noteworthy, we and others demonstrated that astrocyte GLT1 was chronically lost at the injury epicenter following SCI but also downregulated in spinal cord regions distant from the lesion core [103][104][105][106] . Furthermore, experimental data showed that the newlygenerated astrocytes arising during the SCI repair phase lacked GLT1 expression, possibly compromising long-term astrocyte glutamate homeostasis [107] .…”
Section: What Are Spinal Cord Injuries?mentioning
confidence: 67%
See 1 more Smart Citation
“…Failure of long-term extrasynaptic glutamate clearance is suspected to be one major cause of secondary cell loss following SCI. Noteworthy, we and others demonstrated that astrocyte GLT1 was chronically lost at the injury epicenter following SCI but also downregulated in spinal cord regions distant from the lesion core [103][104][105][106] . Furthermore, experimental data showed that the newlygenerated astrocytes arising during the SCI repair phase lacked GLT1 expression, possibly compromising long-term astrocyte glutamate homeostasis [107] .…”
Section: What Are Spinal Cord Injuries?mentioning
confidence: 67%
“…The rationale behind such an approach is based on the findings that, following SCI, astrocyte GLT1 expression and function are compromised, resulting in excitotoxicity-induced cell death during the delayed secondary injury phase [105] . Unpublished data from our group show that transplantation of astrocytes engineered to overexpress GLT1 can prevent excitotoxicity and protect respiratory phrenic motor neurons following cervical SCI.…”
mentioning
confidence: 99%
“…Adult Sprague-Dawley rats received either laminectomy only (uninjured control) or unilateral hemi-contusion SCI at the C4 spinal cord level 1012 . At 5 weeks post-surgery, peak CMAP amplitude recorded from the hemi-diaphragm ipsilateral to the laminectomy/injury site was significantly reduced in SCI rats (Figure 2C) compared to laminectomy-only control (Figure 2B).…”
Section: Representative Resultsmentioning
confidence: 99%
“…Preliminary assessment of a subset of samples yielded a minimum threshold for detecting GFAP expression, which was used to determine the integrated intensity of GFAP expression for all sections. The percent GFAP intensity [(the integrated intensity with minimum threshold divided by the integrated intensity without minimum threshold) multiplied by 100] was calculated per section and averaged per brain [42]. …”
Section: Methodsmentioning
confidence: 99%